Проблеми взаємодії при розслідуванні корупційних злочинів у сфері службової діяльності та професійної діяльності, пов’язаної з наданням публічних послуг - Дорошенко, Ю. К.; Doroshenko, Yu. K. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 2 (101), ч. 1. - С. 194-200, 2023)
Сучасні реалії та стан криміногенної обстановки в країні вимагають принципово нових підходів до взаємодії правоохоронних органів. Сьогодні взаємодія слідчого з іншими органами і підрозділами дедалі активніше здійснюється на всіх можливих рівнях: відомчому, міжвідомчому, міжнародному. Взаємодія при розкритті та розслідуванні кримінальних правопорушень являє собою доволі складну й комплексну форму, яка передбачає реалізацію цілої низки взаємопов’язаних процесуальних та оперативно-розшукових дій і заходів, спрямованих на максимальні досягнення у кримінальному процесі. На основі аналізу нормативно-правових актів зроблено висновок, що чітка регламентація такої взаємодії відсутня.

Modern realities and the state of the criminogenic situation in the country require fundamentally new approaches to the interaction of law enforcement agencies. Today, the interaction of the investigator with other bodies and units is more and more actively carried out at all possible levels, departmental, interdepartmental, international. Interaction in the detection and investigation of criminal offences is a rather complex and comprehensive form that involves a number of interrelated procedural and operational search actions and measures aimed at maximising the achievement of the goals of the criminal process. Cooperation in the investigation of crimes, in particular in the field of official activity, is one of the methods of combating crime, which consists in the coordination and combination in order and on the basis of the law, the efforts of several persons, divisions, bodies, etc. in order to ensure the optimization of the pre-trial investigation of criminal offenses. The specified activity is objectively necessary and often begins from the moment of checking the received information about the commission of a crime. This activity by its nature is very complex, which finds its expression in its phasing. Among the latter, we suggest making a decision about the necessity and expediency of interaction, choosing the form and methods of interaction, procedural consolidation of the decision, direct interaction, and registration of the results of the indicated cooperation. However, the structural clarity of the interaction does not relieve it of the difficulties faced by its participants. This situation is mainly due to the lack of clear regulation of issues related to the organisation and implementation of cooperation in the Criminal Procedure Code of Ukraine. In connection with this, it would be expedient to supplement the specified legal act with a separate section, which would define the concepts, principles, types, forms, methods and procedure of interaction during criminal proceedings.

Современные реалии и состояние криминогенной обстановки в стране требуют принципиально новых подходов к взаимодействию правоохранительных органов. Сегодня взаимодействие следователя с другими органами и подразделениями все активнее осуществляется на всех возможных уровнях: межведомственном, международном. Взаимодействие при раскрытии и расследовании уголовных правонарушений представляет собой достаточно сложную и комплексную форму, предполагающую реализацию целого ряда взаимосвязанных процессуальных и оперативно-розыскных действий и мер, направленных на максимальные достижения в уголовном процессе. На основе анализа нормативно-правовых актов сделан вывод, что четкая регламентация такого взаимодействия отсутствует.
Problems of interaction in the investigation of corruption crimes in the field of official activity and professional activity related to the provision of public services
Keywords: розслідування; корупційні злочини; службова діяльність; професійна діяльність; публічні послуги; взаємодія; кримінальне провадження; криміналістична характеристика; investigation; corruption crimes; official activity; professional activity; public services; interaction; criminal proceedings; forensic characteristics; расследование; коррупционные преступления; служебная деятельность; профессиональная деятельность; публичные услуги; взаимодействие; уголовное производство; криминалистическая характеристика